A Student Counseling Study: The Internalized of Islamic Value in Daily Life - Naqiyah, Najlatun; Kinanti Putri, Diajeng Retno; Mutammima, Dian (Department of Guidance and Counseling, FIP, Undiksha, 2022)
The daily habits of students that have been formed so far in Islamic boarding schools that take place continuously produce positive habits that can be internalized in everyday life. In connection with this, the purpose of this study is to identify Islamic values ​​that can be internalized in daily life, especially to deal with the Covid-19 Pandemic. Santri is a term for students who are in Islamic-based dormitories or commonly referred to as Islamic boarding schools which are cared for by Kyai and Bu Nyai. The population in this study are Islamic boarding schools located in East Java, especially the areas of Madura, Jombang and Probolinggo. This research uses constructivism paradigm with a qualitative approach. The method used is a case study that requires empirical data in Islamic boarding schools. The results of the data through in-depth interview techniques and documentation studies will be analyzed to further develop a narrative about the values ​​that exist in Islamic boarding schools, how to handle them by teachers and reveal the needs of students which can be used as a basis for the development of guidance and counseling in Islamic boarding schools.